Mean Glandular Dose and CDMAM Phantom Image Quality for Siemens Mammomat Inspiration - Hanna Vita Paulana; Kristina Tri Wigati; Djarwani Soeharso Soejoko (Indonesian Association of Physicists in Medicine (AIPM/AFISMI), 2015)
In performing breast screening, a mammography must be capable of imaging microcalcifications with the smallest possible size. However, the mean glandular dose (MGD) should not exceed the recommended limits. To achieve the goal then the utilization of target/filter combination should be adjusted to the thickness of the breast. The evaluation of image quality against variations in target/filter combinations can be done by using CDMAM phantom. There are two methods of CDMAM phantom image quality assessment, and the digital method is considered superior to the manual one. In addition to the evaluation of image quality, MGD received by the phantom was also calculated by multiplying the air kerma value at each thickness with the air kerma conversion factor into MGD. The calculation of MGD follow the equation and convertion factor that published by IAEA Human Health Series No. 17 – Quality Assurance Programme for Digital Mammography, then being compared with three another publication. The best image quality for the phantom thickness below 32 mm achieved by using Mo/Mo target/filter combination, meanwhile for the fantom thickness above 45 mm achieved by using Mo/Rh.